The prickly protection of unaccompanied foreign minors in the European legal mosaic (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The different law between European systems affects the European asylum system for unaccompanied foreign minors and its objectives: the protection of the best interest of the child, the unity of the family and the freedom of movement. The full protection of fundamental rights and human dignity is guaranteed by European Courts with the imposition of positive obligations too. Despite family reunification, the main goal of all Member States, insertion, integration and legal protection are very difficult, because there are management automatisms and regulatory rigidity, due to the complexity of the multicultural environment.
Keywords: Minor age; legal protection; fundamental rights; uniform law; freedom of movement